Comparative Study of The Traditional Fishing Ship Using Cantrang Fishing Gear to be Bottom Longline in Ujungpangkah Waters, Gresik - Muhammad Fikri Anwar; Soffiana Agustin; Yulia Ayu Nastiti (Universitas Muhammadiyah Gresik, 2022)
The variety of fishing gear used by fishermen in Indonesia initiates how to choose the most environmentally friendly fishing gear with good efficiency. The Indonesian government bans cantrang fishing gear because it endangers fish ecosystems and coral reefs. It was then replaced with a longline. This study employs a case study method with descriptive analysis focusing on a case in detail and intensively. In addition to reviewing the environmental impact of using fishing gear cantrang and bottom longline, this study also analyzes the costs required for both tools from manufacture to maintenance, and the revenue of the catch. Based on the research conducted, the capital required for cantrang fishing gear is IDR. 29,450,000 and a longline of IDR. 29,030,000. The profit generated by the cantrang fishing gear for a year is IDR. 56,012,000 while the longline is IDR. 33,836,000. Therefore, it can be concluded that replacing the cantrang fishing gear with a bottom longline is considered simpler, environmentally friendly, inexpensive, and easy to develop.